A Study Of The Classification Of Ultrafine Magnetite And Its Effect On Fine-Coal Dense-Medium Cycloning - G. Ahuja (Society for Mining, Metallurgy & Exploration, 1994)
Tests were conducted to investigate the effects of cyclone geometry, operating conditions, and particle size on magnetite classification. The effects of these parameters on the partition curve for narrow size fractions were studied using a 25mm diameter cyclone cleaning -150 µ m coal. Additional tests were run to investigate the effects of geometry and operating conditions on the slurry, solid, and water splits. The relationship between the relative density of the underflow stream and the relative density of separation was also investigated. This paper presents the results from this study.